2023
DOI: 10.1021/acsomega.2c06501
|View full text |Cite
|
Sign up to set email alerts
|

Lowering Cost Approach for CIGS-Based Solar Cell Through Optimizing Band Gap Profile and Doping of Stacked Active Layers─SCAPS Modeling

Abstract: In this research article, we carry out investigation on compensating the efficiency loss in thin-film CIGS photovoltaic (PV) cell due to absorber coat depth reduction. We demonstrate that the efficiency loss is mainly caused by the disruption of the charge-carrier transport. We propose an architecture engineered with a stepped band gap profile for improving the efficiency of charge-carrier transport and collection. By modifying the gallium content, we tuned the band gap profile of the active layer of a referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Hence, this simulation tool has been used throughout this work, and in this study, the used light source for the testing condition was the AM1_5G 1 light spectrum (100 mW/cm 2 ). SCAPS solves the Poisson’s and continuity equations for electrons and holes for the modeling and these equations are given below d 2 d x 2 normalΨ false( x false) = q ε r false[ p false( x false) n false( x false) + N D N A + N t false] 1 q d d x J n = R n false( x false) G OP false( x false) 1 q d d x J p = G OP false( x false) R n false( x false) …”
Section: Methodsmentioning
confidence: 99%
“…Hence, this simulation tool has been used throughout this work, and in this study, the used light source for the testing condition was the AM1_5G 1 light spectrum (100 mW/cm 2 ). SCAPS solves the Poisson’s and continuity equations for electrons and holes for the modeling and these equations are given below d 2 d x 2 normalΨ false( x false) = q ε r false[ p false( x false) n false( x false) + N D N A + N t false] 1 q d d x J n = R n false( x false) G OP false( x false) 1 q d d x J p = G OP false( x false) R n false( x false) …”
Section: Methodsmentioning
confidence: 99%
“…D n and D p refer to coefficients of electrons and hole diffusion (cm 2 /s), respectively, while μ n and μ p are the mobilities of electrons and holes (cm 2 /(V s)). 77,78 In this work, we initially designed a base device with superstrate configuration FTO/SnO 2 /BaZrS 3 /Cu 2 S/Au, as shown in Figure 1a, using SCAPS-1D (version 3.3.10). The light enters through fluorine-doped tin oxide (FTO) and gets transmitted through the SnO 2 ETL to the absorber.…”
Section: Computational Strategy and Device Descriptionmentioning
confidence: 99%
“…The theoretical calculation relies on three fundamental equations, namely, Poisson’s equation, the carrier continuity equation, and the drift-diffusion equation, which are as follows where q is the charge of electrons ( C ), p is the concentration of holes (cm –3 ), ε is the dielectric constant, n is the concentration of electrons (cm –3 ), φ is the electric potential (V), R is the carrier recombination rate (cm –3 s –1 ), G is the carrier generation rate (cm –3 s –1 ), J p is the current density of holes (mA/cm 2 ), J n is the current density of electrons (mA/cm 2 ). D n and D p refer to coefficients of electrons and hole diffusion (cm 2 /s), respectively, while μ n and μ p are the mobilities of electrons and holes (cm 2 /(V s)). , …”
Section: Computational Strategy and Device Descriptionmentioning
confidence: 99%
“…The current approach aims to provide lasting and concrete solutions to the problems of substitution of active, [1][2][3] window and buffer layers; [4] increasing the conversion yields; [5] determining the factors of stability over time; [6] promoting the use of more abundant materials; and reducing material quantities [7] and production costs. [8,9] It is with the aim of meeting these various challenges that numerous works have been undertaken, notably those of Tchangnwa et al [10,11] on CIGS solar cells, who investigated on the degradation of performance of CdS/CIGSe-based solar cells, highlighted the beneficial effects of alternative buffer layers which enables them to achieve yields above 22% with nanoscale thicknesses for the different layers. Although still nowadays a part of the photovoltaic (PV) community do not acknowledge the existence of a natural build-up of a surface defect layer (SDL) between the CIGS active and the buffer layers when designing CIGS cells, recent work has demonstrated that modeling a free-SDL is likely to provide not reliable and close to experiment results.…”
Section: Introductionmentioning
confidence: 99%